(untitled) (Biological Sciences - PJSIR, 2010)
The vitamin C contents of 5 fruits and 7 vegetables, as a whole and in diced form, were determined by HPLC during cold storage. Results showed a decrease in vitamin C contents during 15 days refrigeration (7 °C) as well as freezing at -20 °C. It was found that fruits are more stable than vegetables since the rate of degradation of vitamin C was higher in vegetables as compared to fruits, either during freezing or refrigeration. During 15 days freezing, fruits showed a decrease of 41.05 - 51.44%, whereas, this loss augmented to 54.12 – 89.10% in vegetables. In addition to this, it was also observed that fruits and vegetables which have peels are less vulnerable to vitamin C degradation; the ratio of degradation of vitamin C in all the fruits studied and potato was not more than 51.44%. In fruits, apple was more susceptible and in vegetables, potato was more stable to vitamin C degradation.